UPAYA MENARIK KONSUMEN BARU MELALUI DIFERENSIASI TEKNOLOGI ONLINE DALAM BISNIS RITEL DI INDONESIA - BRAM SURYAWAN HARSONO, BRAM SURYAWAN HARSONO (Kajian Ilmiah Mahasiswa Manajemen, 2012)
The positive public response to the online store makes an online store as an alternative to expand the retailer sales. For that, more and more retailers are building an online store, and the number of online stores listed on indoshopguide.com until last year reached 139 units divided into12 categories according to the online store of goods sold. Online site is the media liaison between consumers and retailers. The ability of retailers to adopt technology in accordance with ite usability will drive access speed and appearance of the site itself. However,also required the ability to package the technology in the site so that it becomes more attractive to consumers. Retailers must have a differentiation in the application and the application of technology so that it can be an attraction for the consumer to visit the site. Technologies that are applied must be able to add charm and ability to process and transform the site information to visitors so they can attract new customers to visit the site. Keywords : Differentiation,Online Technology, Retailer